Inclusive Green Growth Dataset for African Countries - Isaac K. Ofori; Emmanuel Y. Gbolonyo; Nathanael Ojong (ZBW - Leibniz Information Centre for Economics, 2024)
Tracking the progress of countries in inclusive green growth (IGG) is crucial for shaping effective sustainable development policies. However, comprehensive IGG data is often inaccessible. Accordingly, rigorous empirical contributions in this direction in the context of Africa remain sparse. To address this, we computed IGG scores for 22 African countries from 2000-2020. Our data reveal that only nine of these countries are achieving green and inclusive growth. This dataset equips researchers and institutions to assess IGG progress and identify pathways that African governments can leverage to promote sustainable development.
https://doi.org/10.5281/zenodo.12516392
Keywords: O55; Q01; 330; Africa; Inclusive green growth; IGG; Sustainable Development